1981
DOI: 10.1073/pnas.78.6.3669
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of smooth muscle cells to collagen and their migration toward platelet-derived growth factor.

Abstract: Smooth muscle cells use fibronectin to bind to type I and type Im collagens but bind to type V collagen by a trypsin-resistant intrinsic glycoconjugate. The binding site on type V collagen is located in the aA chain. By using collagen-coated filters in a modified Boyden chamber assay for chemotaxis, it was observed that the platelet-derived growth factor was chemotactic for smooth muscle cells but that several other growth factors were inactive. We suggest that the migration of smooth muscle cells from the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(160 citation statements)
references
References 34 publications
5
154
0
1
Order By: Relevance
“…PDGF is a growth factor for mesenchymal cells such as fibroblasts, smooth muscle cells, and glial cells, which causes cellular migration or proliferation (8). PDGF is mainly produced in megakaryocytes; however, recent findings revealed that many types of cells such as epithelial cells or endothelial cells can also produce PDGF.…”
Section: Signal Transduction Of Mitogen-activated Protein (Map) Kinasmentioning
confidence: 99%
“…PDGF is a growth factor for mesenchymal cells such as fibroblasts, smooth muscle cells, and glial cells, which causes cellular migration or proliferation (8). PDGF is mainly produced in megakaryocytes; however, recent findings revealed that many types of cells such as epithelial cells or endothelial cells can also produce PDGF.…”
Section: Signal Transduction Of Mitogen-activated Protein (Map) Kinasmentioning
confidence: 99%
“…The accumulation of VSMC in the intima results from both cell proliferation and directed migration of VSMCs from the media into the intima [1,2]. These processes are regulated by several growth factors which may be released by cells within the injured vessel or from circulating cells.…”
Section: Introductionmentioning
confidence: 99%
“…VSMC migration is induced by various inflammatory cytokines and chemokines. Plateletderived growth factor (PDGF) is a known potent mitogen abundant in the area of inflammation, and also stimulates VSMC migration (18). It has been reported that PDGFinduced VSMC migration is mediated by MAP kinases, phosphatidylinositol 3-kinase (PI3K), and many other kinases (19,20).…”
Section: Introductionmentioning
confidence: 99%